Method Development and Validation of Gramicidin, Neomycin and Triamcinolone Acetonide Related Substances and their Impurities Quantification through UPLC - Syed, Ibrahim Baje; Nannapaneni, Madhavi (International Journal of Pharmaceutical Investigation, 2025)
Aim/Background To develop and validate a sensitive, accurate, simple, precise and cost-effective receptive and understandable method for concurrent evaluation of Gramicidin, Neomycin and Triamcinolone acetonide and their related contaminants via UPLC. Materials and Methods This method includes the separation using a chromatographic Phenyl column (50 mmx2.1 mm, 1.7 µm). A portable stage of 0.1% TEA (Tri-Ethylamine) and acetonitrile in gradient elution mode with 0.5mL/Temperature and minimum flow rate were employed. At 230 nm, UV observations were made. The limitations for Linearity, quantification and recoveries were discovered being within the allowable range. With UPLC, this method was successfully tested and ICH Q2 (R1) recommendations. Results Gramicidin, Neomycin and Triamcinolone acetonide retention times were observed at 9.315 min,3.979 min and 1.697 min respectively. A gradient elution of Triamcinolone acetonide, Neomycin and Gramicidin involves phenyl column that flows from 0.5 mL/min and the column internal temperature were held constant. Mobile phase % TEA likewise acetonitrile was utilised. UV monitoring was brought at 230 nm. Conclusion This study created an entirely new, straightforward, quick, affordable, sensitive and easily accessible UPLC method for the coincident determination of Triamcinolone acetonide, Neomycin and Gramicidin bulky and ointment dose form. This method has the benefits of being less expensive, assessible, reliable, sensitive and reproducible. Under conditions of oxidation, (Neutral, basic and acidic) hydrolysis, photolysis, thermal stress and medicines degradative activities were investigated. The medications were discovered to be solid underheat, unstable, hydrolysis under acid, alkaline and oxidative circumstances. The Final application of the UPLC method to the commercial formulations followed the ICH recommendations.
Keywords: Gramicidin; Neomycin; Triamcinolone acetonide; Development; UPLC